When Plastic Mimics Stone: An Iatrogenic Bladder Foreign Body-Case Report - Pathania, Prashant; Solanki, Nimit; Dwivedi, Surjeet; Jyoti, Kshitij (Nepal Journal of Medical Sciences, 2026)
Many bladder stones develop over time around foreign bodies. These may include fragments of Foley catheters, forgotten DJ stents, broken guidewires or endoscopic instruments, encrusted sutures, surgical staples, or objects self-introduced by patients with psychiatric disorders. Herein, we report the case of an 80-year-old male who was evaluated for obstructive and irritative lower urinary tract symptoms (LUTS). Imaging suggested a bladder calculus; however, endoscopic intervention revealed and facilitated the removal of an iatrogenically introduced plastic foreign body forming the nidus at the core of the calculus. Although several case reports have described various iatrogenic materials introduced into the urinary bladder masquerading as urinary bladder stones, we have not found a similar case in the available literature.